52‐4: Highest PPI Micro‐OLED Display Sustain for Near‐eye Application. Issue 1 (29th May 2019) - LU, Pengcheng; Huang, Guanda; Yang, Shengji; Chen, Xiaochuan; Dong, Xue; Wang, Hui; Wang, Yanming; Xuan, Minghua; Zhang, Can; Yang, Ming; Wang, Can; Yue, Han
Abstract : The paper presents the highest 5644 PPI Micro‐display completion which performs the FHD resolution in one 0.39 inch display. A 4.5um pixel by sub‐pixel rendering (SPR) technic is applied to achieve the demonstration in reliable and qualified image performance for near‐eye application especially in the field of virtual reality (VR)and augmented reality (AR).